Properties of sandstone for excavation assessments - 412422 Chuan, Kar Wai (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005